Analiza vibracij usmernika alternatorja - Pahor Kos, Vanja (Strojniški vestnik, 2007)
An alternator is subject to large dynamic loads, mainly because of vibrations in the engine and the fixture type, which affect the alternator's lifetime significantly. A certain type of alternator has had problems with its design, primarily as a result of damaged rectifiers caused by vibrations. To identify the reason for the failure an experimental modal analysis (EMA) was performed on the rectifier. The main purpose of the experimental approach was to identify some of the design factors that shorten the lifetime of rectifiers. The basis of the dynamic analysis was frequency-response functions, measured at the rectifier. Based on the measurement data of the original and modified samples of the rectifier, some corrections were made to improve the dynamic characteristics and to extend the lifetime of the rectifier. Useful information for the development of the next generation of the alternatorćs rectifier was obtained. The applied methods can also be extended to other products.
Keywords: vibracije; alternatorji; usmerniki; dinamične lastnosti; modalna analiza